SYSTEM OF CONTROL AND MANAGEMENT OF THE PROCESS OF THE MORTAR SLURRY PREPARATION - D. M. Kukuj; V. F. Odinochko (Литьë и металлургия, 2007)
The technological schema of automatic flow line allowing to prepare with minimum charges of manual labor the refined from solid additives mortar slurry with stable density is presented in the article.